A size-unlimited surface microstructure modification method for achieving high performance triboelectric nanogenerator. (October 2016) - Zhao, Luming; Zheng, Qiang; Ouyang, Han; Li, Hu; Yan, Ling; Shi, Bojing; Li, Zhou
Abstract: Triboelectric nanogenerator (TENG) is a promising mechanical energy harvesting device, which has many advantages such as low cost, high efficiency and easy fabrication. Surface modification on tribo-surface has been proved to be an efficient way to improve the output performance of TENG. However, the existing methods are time-consuming, high-cost and difficult for large-area processing, which, to some extent, limited the industrial production of TENG technology. In this work, we demonstrated a simple, fast and low-cost method, in which the tribo-surfaces of TENG were processed without size limitations to improve its output performance. Through this method, a large-scale treated TENG can be easily achieved and its output voltage and power can be increased by a factor of 3 and 5, respectively, providing us a size-unlimited, low-cost and time-saving surface micro-structure modification method for improving the output of TENG. This work showed great chance for industrial fabrication of TENG, which was crucial for sustainable power supply in the future. Graphical abstract: We can obtain linear micro-structures on tribo-surfaces of TENG without size limitation via a simple, fast sandpaper treatment method. Through this treatment, the output performance of the TENG can be easily increased by several times compared with the untreated one. Highlights: This surface treatment method was proposed to improve the output of TENG. The method is time-saving, low-cost and size-unlimited. Through this method, the output voltage of TENG can be increased by a factor of 3. Through this method, the output power of TENG can be increased by a factor of 5.